Solar Chimney Power Plant in Basrah - Hammadi, Salman Hashim (Basrah Journal for Engineering Sciences, 2009)
The solar chimney is a natural draft device that uses solar radiation to provide upward momentum to the in-flowing air, thereby converting the thermal energy into kinetic energy through an air turbine which in turn can be converted into electrical energy. The main parts of the solar chimney power plant are a large circular solar collector, a tall chimney, and an air turbine. In this paper, a theoretical study was performed to evaluate the performance of a solar chimney power plant system in Basrah City, where sunny days and solar radiation are high. A mathematical model was developed to study the effect of various parameters on the output power of the solar chimney. I1 was found that the output power depends strongly on the chimney tall and the difference between the collector air temperature and the ambient air temperature as well as the outside heat transfer coefficient, which essentially depends on the wind speed.